Power Sneakers - AlQallaf, Hussain (2019)
Walking is a very basic activity that a human could do. it requires a person to lift his foot, move it forward, and then stepping it down and then doing the same for the other leg. Although such an activity is obvious for a regular person, if it were analyzed by engineering students, it could be used for something more than going forward. the pressure that is put in the ground by the feet could be used in a way that benefit the person, using the concepts of piezoelectricity. these concepts would transfer kinetic energy into potential one, and with this potential energy, a person could benefit more from just walking. Such a potential energy could be used to charge a phone, smart watch, or any small electrical device. We aim to make a sneaker that produces electrical energy by using the simple mechanism of steps, along with making this sneaker smart. It is hoped that by this project, people, who suffers from obesity would be encouraged to do physical activities more. Also, we want to take part of "smart clothing" as it is becoming a new trend in the world of technology. But mainly, the aim of this project is to provide a simple electrical source for people who live in poor countries. Basically, the sneaker contains piezo sensors along with a rectifier and a step-up boost to charge a phone and power an Arduino at the same time. It has a Wi-Fi chip that allows the phone to be connected to the sneaker. the project is relatively simple yet innovative, it required the circuit designing skills for two electrical engineering students and the coding and configuring of a computer engineering student, who all hope that symbolically by this project, they could take a step forward to a better world.